Косовський конфлікт в українській та російській історіографії (1992–2010 рр.) - Ткачик, О.О.; Tkachyk, O. O. (My University, 2013)
У статті проаналізовано праці істориків України та Росії щодо албансько-сербського конфлікту в Косово (1992–2010 рр.). Автор систематизує дослідження із цієї проблеми та визначає головні їх тенденції. Особливу увагу приділено з’ясуванню специфіки досліджень історії Косова в Україні та Росії. In the article the analysis of labours of historians of Ukraine and Russia is conducted from Albanian-Serbian to the conflict in Kosovo during 1992–2010. Labours of researchers systematize an author on issue and the main tendencies of researches are determined. The special attention is spared establishment of specific of researches of history of Kosovo in Ukraine and Russia.
Kosovo Conflict in Ukrainian and Russian Historiography.
Keywords: історична славістика; Косовський конфлікт; операція “Союзна сила”; historical slavic studies; conflict in Kosovo; operation “Allied force”; flashbacks of eyewitnesses; right of nations of self-determination; principle of territorial integrity of countries; international precedent; “effect of domino”; “balkanizaciya Europe”; idea of “Large Albania”; право наций на самоопределение; принцип территориальной целостности государств; международный прецедент; “эффект домино”; “балканизация Европы”; идея “Большой Албании”